Proposed model improvement for “mypes” software producers - Amable-Ciudad, Miriam Elizabeth (2017)
This work is based on the results of the research “Analysis of the use of software quality models: a proposal to improve processes in the ‘mypes’ producing software in Lima”, which was supported by the Institute of Scientific Research of the University of Lima. The study characterized “mypes” and showed that they do not have an adequate use of software quality models, both in their processes and products. In addition, these companies recognized that they have problems in their processes and the need to improve them. It was therefore proposed to develop a further research setting a suitable and sustainable process improvement model for each category of “mype”, based on an in-depth analysis of existing quality models, that could be applied throughout the entire software lifecycle: from the establishment of requirements to the quality tests.